THE EFFECT OF BRAND IMAGE, AFTER SALES SERVICE AND PROMOTION MIX ON CONSUMER BUYING BEHAVIOR AT PT. HASJRAT ABADI MANADO TENDEAN - Lolowang, Brenda Kathleen (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Brand image is one of things that are considered by customers when they are about to purchase something while after sales service that is offered by the company is the way to keep its customer loyal and promotion mix is the tool that is used by company to attract customers and reach a target market. The purpose of this study is to investigate the effect of brand image, after sales service and promotion mix on consumer buying behavior of PT. Hasjrat Abadi Manado Tendean. This research uses Multiple Regression Analysis while 110 questionnaires with a Likert-Scale measurement are distributed with only 105 respondents who respond. Findings and results of the study show that there is significant effect of Brand Image and Promotion Mix on Consumer Buying Behavior partially. On the other hand, there is no significant effect of After Sales Service on Consumer Buying Behavior partially. As the recommendation of this research, it is better for the management of PT. Hasjrat Abadi Manado Tendean to set competitive price for the spare part because the result shows that the spare part’s price is still considered by customers as high, and it is better for the management to maintain the Brand Image as well as Promotion Mix. Keywords: brand image, after sales service, promotion mix, consumer buying behavior